Evaluation of the Digides Application System in Public Services in Gebang Ilir Village, Cirebon Regency - Dina Hikmahwati; Rd. Mahendra Haryo Bharoto (Jurnal Indonesia Sosial Teknologi, 2026)
This study aims to assess the effectiveness of the implementation of the Digital Village Application(DIGIDES) in improving public services in Gebang Ilir Village,Cirebon Regency.The problems faced include low digital literacy of the community,limited internet infrastructure,and a lack of experts within the village apparatus. This study used a descriptive qualilative approach with data collection techniques throught in-depth interviews with village heads,operators,and comunity.Research analysisuses the DeLone and McLean Information system Success model (2003) which includes system quality, information quality,Usage,User Satisfaction and benefits.The results of the study indicated that DIGIDES has a  fairly good system and information quality and is able to increase the efficiency of public services in the village.However,the level of use by the community is still relatively low and user satisfaction is not optimal due to technical and social constraints.In addition.there is a gap between e-Government policies at the national level and implementation at the local level. The conclusion of this study shows that DIGIDES is quite effective,but still requires increased training,socialization, internet network improvements,and the provision of self- service facilities to support more transparent,effective and efficient public services